Answer:
(x + y)² =16
Step-by-step explanation:
hello :
(x + y)² = x²+y²+2xy and : x²+y² = 6 xy = 5
(x + y)² = 6+2(5)
(x + y)² =16
F(0)=1
g(1)=(4*1+2)/3 = 6/3=2
hope helped
Answer:
![B=7x^4](https://tex.z-dn.net/?f=B%3D7x%5E4)
Step-by-step explanation:
The given equality is
![-35x^6=(-5x^2)B](https://tex.z-dn.net/?f=-35x%5E6%3D%28-5x%5E2%29B)
Take the term
to the left hand side. This means the term
will be divided by ![(-5x^2)](https://tex.z-dn.net/?f=%28-5x%5E2%29)
![\dfrac{-35x^6}{(-5x^2)}=B](https://tex.z-dn.net/?f=%5Cdfrac%7B-35x%5E6%7D%7B%28-5x%5E2%29%7D%3DB)
Now since both the numerator and denominator have negative sign the value of fraction will be positive.
![\dfrac{35x^6}{(5x^2)}=B](https://tex.z-dn.net/?f=%5Cdfrac%7B35x%5E6%7D%7B%285x%5E2%29%7D%3DB)
Now
and ![x^{6-2}=x^4](https://tex.z-dn.net/?f=x%5E%7B6-2%7D%3Dx%5E4)
![7x^4=B](https://tex.z-dn.net/?f=7x%5E4%3DB)
So, the missing factor ![B=7x^4](https://tex.z-dn.net/?f=B%3D7x%5E4)
Answer:
increase well duhh
Step-by-step explanation:
Answer:
so you have $12.95. then you multiply it by 8% which gives you $13.986. Then you take 10% off of it, which gives you $12.5874.